Bioavailability and Metabolism of Raspberry Ketone with Potential Implications for Obesity Prevention (OR34-05-19). (13th June 2019) - Zhao, Danyue; Yuan, Bo; Kshatriya, Dushyant; Polyak, Andrew; Simon, James; Bello, Nicholas; Wu, Qingli
Abstract: Objectives: Raspberry ketone (RK), the characteristic aromatic phenol derived from red raspberries ( Rubus idaeus L.), has purported anti-obesity properties. This work aims to 1) conduct pharmacokinetic (PK) studies to compare the bioavailability of orally dosed RK among four cohorts of mice: male vs female, lean vs. obese; 2) Characterize major RK metabolites generated in vivo ; 3) Develop targeted metabolomic approaches of bioanalysis. Methods: PK-1: Polyphenol-free diet fed normal-weight C57BL/6 mice (male and female, n = 3–5) received a single dose of RK (200 mg/kg) by gavage. Blood, brain and white adipose tissue (WAT) were then collected at various time-points. 12 h excretion of urine and feces were also collected. PK-2: Another two cohorts of mice were fed on low-fat-diet or high-fat-diet (HFD) for 8 weeks before RK dosing and sample collection. Phenolics in biosamples were extracted and analyzed using ultra-high performance liquid chromatography coupled with triple quadrupole mass spectrometry (UPLC-QqQ/MS). Results: 28 RK-related metabolites including newly discovered RK structurally-related metabolites (SRMs) and typical microbial phenolic acid metabolites (PAMs) were identified and quantified at varying levels in different biosamples using two validated analytical methods. PK results indicated fast absorption of RK (Cmax ∼15 min) and efficient bioconversion into diverse SRMs and PAMs as detected in plasma, brain and WAT specimens. In PK-1 study, total bioavailability including RK and 7 major SRMs, expressed as accumulative area-under-the-curve (AUC, 0–12 h), was lower in females than males (566 vs. 675 nmol/mL * min), which can be explained by the faster absorption and elimination in females. In PK-2 study, total bioavailability in obese mice was almost doubled that of lean mice (1197 vs. 679 nmol/mL * min), while the peak time of RK metabolites and elimination half-lives were generally delayed. Moreover, the rapid and remarkable accumulation of RK and its metabolites in brain and WAT are suggestive of RK's direct effects on lipid-rich tissues. Conclusions: Orally administered RK is highly bioavailable, including in the brain and WAT, and are rapidly metabolized in mice. Our findings are critical for elucidating the sites and mechanisms of action of RK for long-term management of diet-induced obesity. Funding Sources: This work was supported by the NIH R01AT008933. Supporting Tables, Images and/or Graphs: